LAND ALLOCATION ANALYSIS OF THE UPHELESS BELAWAN RIVER BASIN (DAS) IN RELATION TO SPATIAL PLANNING - Rizki Hany; Abdul Rauf; Bejo Slamet (RADJA PUBLIKA, 2024)
Regional development must be balanced and sustainable, particularly in managing the Belawan Watershed, which includes Deli Serdang and Medan. Proper spatial planning is essential to maintaining the upstream and downstream ecosystems and ensuring environmental sustainability. This study aims to analyze the availability of agricultural land in the upper Belawan Watershed to meet human needs. Additionally, it seeks to provide guidance on land allocation within spatial planning and develop sustainable land allocation recommendations for the future. The research methodology employs a qualitative descriptive approach to explain land use and a quantitative approach for presenting numerical data that can be processed using simple calculations. The study concludes that nearly all land in the upper Belawan sub-watershed has been utilized, with only 0.6% remaining as an ecological buffer. The most significant land-use change has been the conversion of production forests into plantations, covering an area of ​​4,808.70 hectares. Future spatial planning must balance land use with environmental conservation.